The Analysis of Election Criminal Actions Around 2019 in Banjarnegara - Endro Wibowo Aji; Rachmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
The purpose of this research is to find out what factors are hindering in enforcing the 2019 election criminal law in Banjarnegara Regency and how the solution is carried out by the Bawaslu of Banjarnegara Regency in enforcing the election criminal law in 2019. The research method is taken using sociological juridical with descriptive specifications done to retrieve the facts that happened. The results showed that in the administration of elections, law enforcement against criminal acts in legislative elections encountered many obstacles such as: the failure to fulfill the formal and material requirements of the alleged violation of election criminal acts, both from the findings of supervisors and public reports, made it difficult to follow up on the alleged violations; multi-interpretative regulations cause human resource difficulties in applying the articles that must be suspected in suspected election violations; disagreements between institutions in the integrated law enforcement center (Gakkumdu); limited time for handling election crimes. Bawaslu of Banjarnegara Regency in overcoming obstacles keeps trying as much as possible to follow up on suspected violations, maximizing preventive actions through various channels, media, and always coordinates both vertically with Bawaslu of Central Java Province and coordinates horizontally with all related parties in Banjarnegara Regency in the framework of minimize potential violations.